PENGARUH KEBAKARAN DAN WAKTU SETELAH TERBAKAR TERHADAP MAKROFAUNA TANAH GAMBUT DI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Sugiarto, Sugiarto; Wawan, Wawan; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to compare macrofauna of burnt and unburned peat soil and to know the effect of time increase after fire to macrofauna peat soil. This research was conducted by survey method, sampling for soil macrofauna data determined by purposive random sampling method that is by choosing the location in accordance with the purpose of research. The soil samples were taken on unburnt peatland, in peat a week after fires and in peat 4 months after fires with a capture area of 1 m x 1 m at a depth of up to 15 cm taken 6 samples so that there were 18 samples. The data obtained from the results of research and calculations are listed in table form. Then the data is analyzed statistically descriptive. The results of this study indicate the type and number of macrofauna individual soil on peat is not burned more than peat a week after the fire and, peat 4 months after the fire. Time-increasing effects on peat a week after a fire have increased the type and number of macrofauna because macrofauna proliferate in peat 4 months after the fire.Keywords:Macrofauna, Fire and Peat.